2008
DOI: 10.5194/angeo-26-583-2008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosphere-ionosphere coupling during periods of extended high auroral activity: a case study

Abstract: Abstract.Results are presented from a case study of a plasma boundary crossing by the Cluster spacecraft during an extended period of high auroral activity. The boundary between the magnetotail lobe region of the Southern Hemisphere and the plasma sheet boundary layer, was characterized by intense electric and magnetic field variations, structured upward accelerated ion beams, narrow-scale large field-aligned Poynting fluxes directed upward away from the ionosphere, and a relatively sharp plasma density gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The quasi-static electric field structures observed by Cluster were also associated with Earthward Poynting fluxes (e.g., Johansson et al, 2004), although one event with Poynting flux away from Earth has been reported (Liléo et al, 2008). The Cluster events were typically located at plasma boundaries Johansson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The quasi-static electric field structures observed by Cluster were also associated with Earthward Poynting fluxes (e.g., Johansson et al, 2004), although one event with Poynting flux away from Earth has been reported (Liléo et al, 2008). The Cluster events were typically located at plasma boundaries Johansson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The association of magnetospheric interfaces with these strong electric fields has been demonstrated in various case studies (e.g. Vaivads et al, 2003;Johansson et al, 2006;Kullen et al, 2008;Liléo et al, 2008). Note that the electrostatic model presented here predicts that transverse ionospheric electric fields can exist on both sides of an arc, which must give rise to oppositely directed plasma convection along the arc (Kullen et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Stronger converging fields lead to higher parallel potential differences, stronger upward field-aligned currents, even higher ionospheric conductivity, and accelerated upgoing ions, all typical of discrete auroral arcs (e.g. Lyons, 1981;Carlson et al, 1998;Vaivads et al, 2003;Figueiredo et al, 2005;Liléo et al, 2008;Echim et al, 2009). A statistical study by Johansson et al (2007) points out that the scale sizes of intense electric field signatures, of the field-aligned currents, and of the density gradients observed above the auroral zone at 5-7 R E geocentric distance were compatible, supporting the overall picture of a magnetospheric interface associated with the arc structure, and determining its thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation